Microservice Architecture: A Tertiary Study - Costa, Diego Ivo Campos; Silva Filho, Eduardo Pereira e; Silva, Reginaldo Florencio da; Gama, Thiago Dias de C. Quaresma; Cortés, Mariela I. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2020: Anais do XIV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2020)
Context. The large-scale use of microservices and their increasing adoption in the industry in recent years has motivated researches on the most diverse aspects related to microservice-based development. However, as it is a relatively new topic, there is still no consolidated body of knowledge in the area. Objective. The present work intends to investigate the current state of research on microservices based on the formulation of six research questions covering fundamental aspects, such as: main interest topics and adopted standards, techniques and tools have been used and application areas. Method. From four digital libraries, 22 secondary studies were selected as a data source, which were analyzed and synthesized in the present study following the proposed research protocol. Results. Among the main topics of interest addressed, we highlight researches related to the applicability of microservice architecture, both by industry and academia. Results indicated that standards focus on challenges related to communication have been the most commonly considered by researchers of the area. Finally, the predominance in the use of the Docker container and the presence of DevOps practices in the automation of operations are noteworthy. Conclusions. The present mapping study points to some directions of research based on the identified gaps, such as modeling and testing of microservice applications, and addressing security aspects. Another promising point to be explored involves the combined use of microservice architecture with other related concepts such as IoT, smart cities, FOG computing and reactive systems, in order to reinforce the use of microservices, as well as creating new solutions and challenges to be researched.